Glycolysis inhibition ameliorates brain injury after ischemic stroke by promoting the function of myeloid-derived suppressor cells. (May 2022) - Yan, Jingwei; Li, Anqi; Chen, Xianglin; Cao, Kaixiang; Song, Mingchuan; Guo, Shuai; Li, Zou; Huang, Shuqi; Li, Ziling; Xu, Danghan; Wang, Yong; Dai, Xiaoyan; et al.
Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells which are immunosuppressive and glycolytically inactive in inflammatory diseases. However, it is unknown whether MDSCs contribute to ischemic stroke and how glycolysis regulates MDSC function in such a context. Here, we showed that MDSCs arise in the blood of patients at early phase of stroke. Similar results were observed in temporary middle cerebral artery occlusion-induced cerebral ischemic mice. Pharmaceutical exhaustion of MDSCs aggravated, while adoptive transfer of MDSCs rescued the ischemic brain injury. However, the differentiation of MDSCs into immunopotent myeloid cells which coincides with increased glycolysis was observed in the context of ischemic stroke. Mechanistically, the glycolytic product lactate autonomously induces MDSC differentiation through activation of mTORC1, and paracrinely activates Th1 and Th17 cells. Moreover, gene knockout or inhibition of the glycolytic enzyme PFKFB3 increased endogenous MDSCs by blocking their differentiation, and improved ischemic brain injury. Collectively, these results revealed that glycolytic switch decreases the immunosuppressive and neuroprotective role of MDSCs in ischemic stroke and pharmacological targeting MDSCs via glycolysis inhibition constitutes a promising therapeutic strategy for ischemic stroke. Graphical Abstract: ga1